What Drives Public Health Care Expenditure Growth? Evidence from Swiss Cantons, 1970-2012 - Thomas Braendle; Carsten Colombier (University of Basel, Center of Business and Economics (WWZ), 2015)
A better understanding of the determinants of public health care expenditures is key to designing effective health policies. We integrate supply and demand-side determinants, factors from political economy and health policy reforms into an empirical analysis of the highly decentralized Swiss health care system. We compile a novel data set of the cantonal health care expenditure in Switzerland spanning the period 1970 - 2012. Using dynamic panel estimation methods, we find that per capita income, the unemployment rate and the share of foreigners are positively related to public health care expenditure growth. With regard to political economy aspects, public health care expenditures increase with the share of women elected to parliament. However, institutional restrictions for politicians, such as fiscal rules and mandatory fiscal referenda, do not appear to limit public health care expenditure growth.
Keywords: H75; D72; C23; I18; 330; Public health care expenditure; Panel data; Fiscal rules; Political selection